Synchrotron radiation circular dichroism spectroscopy reveals that gold and silver nanoparticles modify the secondary structure of a lung surfactant protein B analogue. Issue 9 (10th February 2023) - Buckley, Alison; Warren, James; Hussain, Rohanah; Smith, Rachel
Abstract : Synchrotron radiation circular dichroism shows that gold and silver nanoparticles modify the secondary structure of lung surfactant protein-B analogue SP-B1–25 . Abstract : Inhaled nanoparticles (NPs) depositing in the alveolar region of the lung interact initially with a surfactant layer and in vitro studies have demonstrated that NPs can adversely affect the biophysical function of model pulmonary surfactants (PS), of which surfactant protein B (SP-B) is a key component. Other studies have demonstrated the potential for NPs to modify the structure and function of proteins. It was therefore hypothesised that NPs may affect the biophysical function of PS by modifying the structure of SP-B. Synchrotron radiation circular dichroism (SRCD) spectroscopy was used to explore the effect of various concentrations of gold nanoparticles (AuNPs) (5, 10, 20 nm), silver nanoparticles (AgNPs) (10 nm) and silver citrate on the secondary structure of surfactant protein B analogue, SP-B1–25, in a TFE/PB dispersion. For Au and Ag NPs the SRCD spectra indicated a concentration dependent reduction in the α-helical structure of SP-B1–25 (5 nm AuNP ≈ 10 nm AgNP ≫ 10 nm AuNP > 20 nm AuNP). For AuNPs the effect was greater for the 5 nm size, which was not fully explained by consideration of surface area. The impact of the 10 nm AgNPs was greater than that of the 10 nm AuNPs and the effect of AgNPs was greater than that of silver citrate at equivalent Ag mass concentrations. For 10 nm AuNPs, SRCD spectra for dispersions in, the more physiologically relevant, DPPC showed a similar concentration dependent pattern. The results demonstrate the potential for inhaled NPs to modify SP-B1–25 structure and thus potentially adversely impact the physiological function of the lung, however, further studies are necessary to confirm this.